Redefining the role of language in a globalized world - Wang, Ailing (College teacher) (Advances in linguistics and communication studies (ALCS) book series., 2021)
""This book explores the role language will play in a globalized world and how language changes over time through its interdependent relationship with technology"--Provided by publisher"--